Factors Affecting the Adoption of Digital Marketing by SMEs in the Context of Sri Lanka - Madurapperuma, R. K.; Colombage, V.K. (NSBM Green University, 2022)
The business world’s shift into the digital age has only been fast-tracked by the COVID-pandemic, which forced companies to conduct business via digital means, and digital marketing is one of its many latest trends. This study investigates factors that motivate SMEs to adopt digital marketing strategies, specifically social media marketing, by SMEs in Sri Lanka. the researcher has selected the TOE framework as the basis for this study. After a thorough literature review, the researcher proposes a mixed research strategy using online surveys and interviews to answer the research question. The researcher has built the research plan so that limitations are minimized.